2018
DOI: 10.1007/s40843-017-9201-4
|View full text |Cite
|
Sign up to set email alerts
|

A breakthrough in direct conversion of methane to oxygenates under mild conditions

Abstract: Methane is an attractive C1 resource for production of value-added chemicals. The current industrial utilization of methane involves indirect route via preliminary oxidation to syngas (a mixture of CO and H 2 ) that can be converted to desired products [1]. Such two-stage process is energy-intensive. Considerable efforts have been devoted to developing catalytic processes that can efficiently and directly transform methane through oxidative or non-oxidative pathways [2,3]. Since the pioneering work of methane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Thesingle rhodium atom catalyst has received increasing interest in recent years in heterogeneous catalysis. [19] It was found that the isolated Rh atoms anchoring on the supports of zeolite, [19a-c] titania, [19a] and zirconia [19d] can catalyze the oxidation of methane to acetic acid or methanol by using strong oxidants such as O 2 and H 2 O 2 at 423 K. The dispersed Rh atoms in the cationic states (+ 1, + 3, and + 4) were proposed as the active sites to selectively activate the first CÀHb ond of methane to form the important CH 3 intermediate,w hich then reacted with the adsorbed O 2 and H 2 O 2 to produce the oxygenated products.I nc ontrast to the heterogeneous catalysis,o ur gas phase study reveals an ovel route for direct methane conversion:t he single Rh atom supported on av anadium oxide cluster (RhVO 3 À )c an mediate the catalytic oxidation of methane to methanol by using the soft oxidant of CO 2 .T he NBO analysis indicated that the electron configuration of the Rh atom in RhVO 3 À cluster is [5s(0.75)4d(8.17)5p(0.07)5d(0.01)].T he total number of electrons of such electron configuration is almost equal to those of bare Rh atom (5s 1 4d 8 ). Thus,t he selective methane activation by RhVO 3 À occurs over the Rh atom in the neutral state.Subsequently the formed CH 3 intermediate reacts with the hydroxyl group to generate CH 3 OH after CO 2 reduction by the Rh À Vb ond.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thesingle rhodium atom catalyst has received increasing interest in recent years in heterogeneous catalysis. [19] It was found that the isolated Rh atoms anchoring on the supports of zeolite, [19a-c] titania, [19a] and zirconia [19d] can catalyze the oxidation of methane to acetic acid or methanol by using strong oxidants such as O 2 and H 2 O 2 at 423 K. The dispersed Rh atoms in the cationic states (+ 1, + 3, and + 4) were proposed as the active sites to selectively activate the first CÀHb ond of methane to form the important CH 3 intermediate,w hich then reacted with the adsorbed O 2 and H 2 O 2 to produce the oxygenated products.I nc ontrast to the heterogeneous catalysis,o ur gas phase study reveals an ovel route for direct methane conversion:t he single Rh atom supported on av anadium oxide cluster (RhVO 3 À )c an mediate the catalytic oxidation of methane to methanol by using the soft oxidant of CO 2 .T he NBO analysis indicated that the electron configuration of the Rh atom in RhVO 3 À cluster is [5s(0.75)4d(8.17)5p(0.07)5d(0.01)].T he total number of electrons of such electron configuration is almost equal to those of bare Rh atom (5s 1 4d 8 ). Thus,t he selective methane activation by RhVO 3 À occurs over the Rh atom in the neutral state.Subsequently the formed CH 3 intermediate reacts with the hydroxyl group to generate CH 3 OH after CO 2 reduction by the Rh À Vb ond.…”
Section: Angewandte Chemiementioning
confidence: 99%